Subjective wellbeing as a public policy approach and instrument: An analytic literature review - Castellanos Cereceda, Roberto (Estado, Gobierno y Gestión Pública, 2012)
In this paper we analyze the utility that the subjective wellbeing approach brings to the study, analysis and design of public policy. It argues that the subjective wellbeing approach offers new ways to test basic assumptions of the economic and social analysis of human behavior; offers analytical tools that provide a different and complementary perspective to traditional measures and approaches regarding the aspects that matter most to the population in their development process; and provides a set of important reflections regarding the implications of the study of happiness and life satisfaction for different types of public policy and in different fields of government action. These aspects are analyzed through a historical tracing of the origins of the systematic study of subjective wellbeing and a literature review to identify issues addressed, tools developed and public policies involved.